Bile acid sequestrants for primary prevention of ischaemic heart disease in heterozygous familial hypercholesterolaemia - Ryan, Aidan (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness and safety of BAS in the primary prevention of IHD in people with HeFH.